Sub-optimal host plants have developmental and thermal fitness costs to the invasive fall armyworm - Mubayiwa, Macdonald; Machekano, Honest; Chidawanyika, Frank; Mvumi, Brighton M.; Segaiso, Bame; Nyamukondiwa, Casper (Frontiers in Insect Science, 2023)
The fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) is a global invasive pest of cereals. Although this pest uses maize and sorghum as its main hosts, it is associated with a wide range of host plants due to its polyphagous nature. Despite the FAW's polyphagy being widely reported in literature, few studies have investigated the effects of the non-preferred conditions or forms (e.g., drought-stressed forms) of this pest’s hosts on its physiological and ecological fitness. Thus, the interactive effects of biotic and abiotic stresses on FAW fitness costs or benefits have not been specifically investigated. We therefore assessed the effects of host plant quality on the developmental rates and thermal tolerance of the FAW. Specifically, we reared FAW neonates on three hosts (maize, cowpeas, and pearl millet) under two treatments per host plant [unstressed (well watered) and stressed (water deprived)] until the adult stage. Larval growth rates and pupal weights were determined. Thermal tolerance traits viz critical thermal maxima (CTmax), critical thermal minima (CTmin), heat knockdown time (HKDT), chill-coma recovery time (CCRT), and supercooling points (SCPs) were measured for the emerging adults from each treatment. The results showed that suboptimal diets significantly prolonged the developmental time of FAW larvae and reduced their growth rates and ultimate body weights, but did not impair their full development. Suboptimal diets (comprising non-cereal plants and drought-stressed cereal plants) increased the number of larval instars to eight compared to six for optimal natural diets (unstressed maize and pearl millet). Apart from direct effects, in all cases, suboptimal diets significantly reduced the heat tolerance of FAWs, but their effect on cold tolerance was recorded only in select cases (e.g., SCP). These results suggest host plant effects on the physical and thermal fitness of FAW, indicating a considerable degree of resilience against multiple stressors. This pest’s resilience can present major drawbacks to its cultural management using suboptimal hosts (in crop rotations or intercrops) through its ability to survive on most host plants despite their water stress condition and gains in thermal fitness. The fate of FAW population persistence under multivariate environmental stresses is therefore not entirely subject to prior environmental host plant history or quality.